Genetic and Environmental Contributions to Stability in Adult Obsessive Compulsive Behavior. (18th December 2014) - Zilhão, Nuno R.; Smit, Dirk J. A.; den Braber, Anouk; Dolan, Conor V.; Willemsen, Gonneke; Boomsma, Dorret I.; Cath, Danielle C.
Abstract : This study investigates the relative contribution of genetic and environmental factors to the stability of obsessive-compulsive (OC) symptoms in an adult population-based sample. We collected data from twin pairs and their siblings, using the Padua Inventory Revised Abbreviated, from the population-based Netherlands Twin Register (NTR) in 2002 ( n = 10.134) and 2008 ( n = 15.720). Multivariate twin analyses were used to estimate the stability of OC symptoms as a function of genetic and environmental components. OC symptoms were found to be highly stable, with a longitudinal phenotypic correlation of 0.63. Longitudinal broad sense heritability was found to be 56.0%. Longitudinal correlations for genetic ( r = 0.58 for additive, r = 1 for non-additive genetic factors) and non-shared environment ( r = 0.46) reflected stable effects, indicating that both genes and environment are influencing the stability of OC symptoms in adults. For the first time, evidence is reported for non-additive genetic effects on the stability of OC symptoms. In conclusion, this study showed that OC symptoms are highly stable across time in adults, and that genetic effects contribute mostly to this stability, both in an additive and non-additive way, besides non-shared environmental factors. These data are informative with respect to adult sample selection for future genetic studies, and suggest that gene–gene interaction studies are needed to further understand the dominance effect found in this study.